Consumer demand for dairy products in Ukraine: factors and incentives - Davydchuk, Mariia; Nikitenko, Olga (My University, 2023)
Dairy products are an important source of nutrition, rich in proteins, vitamins and minerals, which are necessary for the proper functioning of the body. In addition, it is an integral part of many dishes and drinks that we consume every day. That is why it is advisable to analyze the factors of demand for various dairy products and for products which are famous under TM Pyriatyn, in particular. The research uses such methods as observation, analysis, and expert evaluations. It аlso includes statistical data, information about the market and competitors, the results of previous studies, comparison, generalization and systematization.

Молочні продукти є важливим джерелом живлення, багатим на білки, вітаміни та мінерали, необхідні для нормального функціонування організму. Крім того, він є невід'ємною частиною багатьох страв і напоїв, які ми вживаємо щодня. Тому доцільно проаналізувати фактори попиту на різноманітну молочну продукцію, зокрема на продукцію, яка відома під ТМ «Пирятин». У дослідженні використовуються такі методи, як спостереження, аналіз, експертні оцінки. Він також включає статистичні дані, інформацію про ринок і конкурентів, результати попередніх досліджень, порівняння, узагальнення та систематизацію.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; consumer demand; nutritional value; range of products; молочна продукція; споживчий попит; харчова цінність; асортимент продукції